Exploring Sadness and Hope in the Lyrics of the Pop Song “Diary Depressiku” by Last Child: A Semiotic Analysis - Dzulkhaffi Muhammad Arieful Husna; Otong Setiawan Djuharie (INDO PUBLISHING, 2025)
This research explores the expression of emotion and hope in the lyrics of the pop song “Diary Depressiku” by Last Child through a semiotic analysis approach. The song, inspired by the vocalist's personal experience, reflects deep emotional struggles stemming from family problems, especially parental divorce and longing for affection. Using a qualitative method, this research examines the semantic features of the song's lyrics to reveal how feelings of sadness, despair, envy, and ultimately hope are constructed and conveyed. The analysis revealed that the lyrics use a variety of emotive language and metaphors to depict the protagonist's internal conflicts and her journey towards acceptance and resilience. In addition, the research highlights how the song not only articulates personal pain but also offers a sense of hope and encouragement to listeners facing similar situations. The findings contribute to a deeper understanding of how pop music lyrics can serve as a medium for emotional expression and healing, especially for young listeners experiencing family challenges.